EFEKTIFITAS PENGEMBANGAN MODEL PEMBELAJARAN BERBASIS LABORATORIUM PADA MAHASISWA PENDIDIKAN SEJARAH IKIP PGRI PONTIANAK - suwarni, suwarni; Lestari, Emi Tipuk Lestari Tipuk (Universitas PGRI Yogyakarta, 2021)
The purpose of this study 1) Measuring learning outcomes in the control class, 2) Measuring learning outcomes in the experimental class, 3) Measuring the effect of learning outcomes in the control and experimental classes, 4) Measuring the influence of using the History Education laboratory for students. Method used is an experiment with a quasi experimental research design and a Posstest-Only Control Design. The results of this study were 1) The average student learning outcomes in the control class were 66.33 which was classified as sufficient, 2) The average learning outcomes of students who were taught or in the experimental class were 77.42 which were classified as good, 3) The average significant difference was The average learning outcomes of the control class and the experimental class used the t-test parametric statistical test. Because tcount> ttable or 4.43> 1.996, then Ha is accepted at the 5% significance level. So the conclusion is that there is a difference in the average value of the control class and the average value of the experimental class, 4) Based on calculations using the effect size, it isÂ obtained that Es <80, or Es = 0.55, it can be concluded that the use of historical education laboratories is moderate and has an effect on student learning outcomes.Â